Isolation and Characterization of a Nucleopolyhedrovirus from Rachiplusia nu (Guenée) (Lepidoptera: Noctuidae) - Rodriguez, Vanina Andrea (2012)
Rachiplusia nu (Guenée) (Lepidoptera: Noctuidae) is an important pest of vegetable crops widely distributed in South America. At present, its control is based on the use of broad spectrum chemical insecticides. In order to develop a more selective alternative to be applied in integrated or organic pest management programs, we isolated and characterized a baculovirus that infects R. nu, denominated RanuMNPV (Rachiplusia nu multiple nucleopolyhedrovirus) in view of its morphology and pattern of infection. According to optical microscope images of infected in vitro cell cultures, data from bioassays carried out with various species of larvae, and DNA sequences from p74, polyhedrin, v-cathepsin, v-chitinase, lef8 and lef9 genes, this isolate could be considered as a variant of Autographa californica MNPV with a different host range.